Origin and Evolution of Earth: Research Questions for a Changing Planet - National Research Council (The National Academies Press, 2008)
Questions about the origin and nature of Earth and the life on it have long preoccupied human thought and the scientific endeavor. Deciphering the planet's history and processes could improve the ability to predict catastrophes like earthquakes and volcanic eruptions, to manage Earth's resources, and to anticipate changes in climate and geologic processes. At the request of the U.S. Department of Energy, National Aeronautics and Space Administration, National Science Foundation, and U.S. Geological Survey, the National Research Council assembled a committee to propose and explore grand questions in geological and planetary science. This book captures, in a series of questions, the essential scientific challenges that constitute the frontier of Earth science at the start of the 21st century.

Review of NASA's Exploration Technology Development Program: An Interim Report - National Research Council (The National Academies Press, 2008)
To meet the objectives of the Vision for Space Exploration (VSE), NASA must develop a wide array of enabling technologies. For this purpose, NASA established the Exploration Technology Development Program (ETDP). Currently, ETDP has 22 projects underway. In the report accompanying the House-passed version of the FY2007 appropriations bill, the agency was directed to request from the NRC an independent assessment of the ETDP. This interim report provides an assessment of each of the 22 projects including a quality rating, an analysis of how effectively the research is being carried out, and the degree to which the research is aligned with the VSE. To the extent possible, the identification and discussion of various cross-cutting issues are also presented. Those issues will be explored and discussed in more detail in the final report.

A Constrained Space Exploration Technology Program: A Review of NASA's Exploration Technology Development Program - National Research Council
In January 2004, President George W. Bush announced the Vision for Space Exploration (VSE), which instructed NASA to \

Agriculture, Forestry, and Fishing Research at NIOSH: Reviews of Research Programs of the National Institute for Occupational Safety and Health - National Research Council; Institute of Medicine (The National Academies Press, 2008)
The agriculture, forestry, and fishing sectors are the cornerstone of industries that produce food, fiber, and biofuel. The National Institute for Occupational Safety and Health (NIOSH) conducts research in order to improve worker safety and health in these sectors. This National Research Council book reviews the NIOSH Agriculture, Forestry, and Fishing Program to evaluate the 1) relevance of its work to improvements in occupational safety and health and 2) the impact of research in reducing workplace illnesses and injuries. The assessment reveals that the program has made meaningful contributions to improving worker safety and health in these fields. To enhance the relevance and impact of its work and fulfill its mission, the NIOSH Agriculture, Forestry, and Fishing Program should provide national leadership, coordination of research, and activities to transfer findings, technologies, and information into practice. The program will also benefit from establishing strategic goals and implementing a comprehensive surveillance system in order to better identify and track worker populations at risk.

Analysis and Recommendations for Developing Integrated Airport Information Systems - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2008)
TRB2019s Airport Cooperative Research Program (ACRP) Web-Only Document 1: Analysis and Recommendations for Developing Integrated Airport Information Systems is a summary of the efforts associated with the development of ACRP Report 13: Integrating Airport Information Systems. ACRP Report 13 is designed to help airport mangers and information technology professionals address issues associated with integrating airport information systems.

Treatment of Posttraumatic Stress Disorder: An Assessment of the Evidence - Institute of Medicine (The National Academies Press, 2008)
Mental disorders, including posttraumatic stress disorder (PTSD), constitute an important health care need of veterans, especially those recently separated from service. Treatment of Posttraumatic Stress Disorder: An Assessment of the Evidence takes a systematic look the efficacy of pharmacologic and psychological treatment modalities for PTSD on behalf of the Department of Veterans Affairs. By reviewing existing studies in order to draw conclusions about the strength of evidence on several types of treatment, the Committee on the Treatment of Posttraumatic Stress Disorder found that many of these studies were faulty in design and performance, and that relatively few of these studies have been conducted in populations of veterans, despite suggestions that civilian and veteran populations respond differently to various types of treatment. The committee also notes that the evidence is scarce on the acceptability, efficacy, or generalizability of treatment in ethnic and cultural minorities, as few studies stratified results by ethnic background. Despite challenges in the consistency, quality, and depth of research, the committee found the evidence sufficient to conclude the efficacy of exposure therapies in treating PTSD. The committee found the evidence inadequate to determine efficacy of different types of pharmacotherapies, of three different psychotherapy modalities, and of psychotherapy delivered in group formats. The committee also made eight critical recommendations, some in response to the VA's questions related to recovery and the length and timing of PTSD treatment, and others addressing research methodology, gaps in evidence and funding issues.

NASA's Elementary and Secondary Education Program: Review and Critique - National Research Council (The National Academies Press, 2008)
The federal role in precollege science, technology, engineering, and mathematics (STEM) education is receiving increasing attention in light of the need to support public understanding of science and to develop a strong scientific and technical workforce in a competitive global economy. Federal science agencies, such as the National Aeronautics and Space Administration (NASA), are being looked to as a resource for enhancing precollege STEM education and bringing more young people to scientific and technical careers. For NASA and other federal science agencies, concerns about workforce and public understanding of science also have an immediate local dimension. The agency faces an aerospace workforce skewed toward those close to retirement and job recruitment competition for those with science and engineering degrees. In addition, public support for the agency's missions stems in part from public understanding of the importance of the agency's contributions in science, engineering, and space exploration. In the NASA authorization act of 2005 (P.L. 109-555 Subtitle B-Education, Sec. 614) Congress directed the agency to support a review and evaluation of its precollege education program to be carried out by the National Research Council (NRC). NASA's Elementary and Secondary Education Program: Review and Critique includes recommendations to improve the effectiveness of the program and addresses these four tasks: 1. an evaluation of the effectiveness of the overall program in meeting its defined goals and objectives; 2. an assessment of the quality and educational effectiveness of the major components of the program, including an evaluation of the adequacy of assessment metrics and data collection requirements available for determining the effectiveness of individual projects; 3. an evaluation of the funding priorities in the program, including a review of the funding level and trend for each major component of the program and an assessment of whether the resources made available are consistent with meeting identified goals and priorities; and 4. a determination of the extent and effectiveness of coordination and collaboration between NASA and other federal agencies that sponsor science, technology, and mathematics education activities.

Review of the Naval Sea Systems Command (NAVSEA) Draft Memorandum: NAVSEA's 21st Century Engagement, Education, and Technology Initiative (The National Academies Press, 2008)

Review of the Federal Railroad Administration Research and Development Program: Letter Report April 2008 - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2008)
TRB2019s Committee for Review of the Federal Railroad Administration Research and Development Program has issued its first letter report to Joseph Boardman, Administrator of the Federal Railroad Administration (FRA). The letter report explores stakeholder involvement in the FRA R&D program, examines development of a project evaluation process, reviews research priorities from a 2006 workshop, highlights the role of academic research in railroad engineering and transportation, and identifies potential future committee meetings and activities.

Initial Guidance for an Update of the National Vaccine Plan: A Letter Report to the National Vaccine Program Office - Institute of Medicine (The National Academies Press, 2008)
This book is the Institute of Medicine's response to the first part of the statement of task asking for a review of the 1994 National Vaccine Plan. The Committee on the Review of Priorities in the National Vaccine Plan reviewed the goals, objectives, strategies, and anticipated outcomes presented in the plan; their findings are contained in this book. In the first section of the book, the committee examines what has changed in the broader social, policy, and economic context of vaccine development and immunization, and highlights several areas where noteworthy progress has been made, particularly by federal agencies. The committee acknowledges that progress in developing and delivering vaccines has benefited from essential contributions by other stakeholders, including researchers, manufacturers, state and local public health agencies, and health care providers. In the second section of the book, the committee uses what it learned from reviewing the 1994 plan and the process of preparing it to distill key elements. Based on these elements, the committee offers guidance to NVPO and its partners on developing the update to the national vaccine plan.

Using the American Community Survey for the National Science Foundation's Science and Engineering Workforce Statistics Programs - National Research Council (The National Academies Press, 2008)
The National Science Foundation (NSF) has long collected information on the number and characteristics of individuals with education or employment in science and engineering and related fields in the United States. An important motivation for this effort is to fulfill a congressional mandate to monitor the status of women and minorities in the science and engineering workforce. Consequently, many statistics are calculated by race or ethnicity, gender, and disability status. For more than 25 years, NSF obtained a sample frame for identifying the target population for information it gathered from the list of respondents to the decennial census long-form who indicated that they had earned a bachelors or higher degree. The probability that an individual was sampled from this list was dependent on both demographic and employment characteristics. But, the source for the sample frame will no longer be available because the census long-form is being replaced as of the 2010 census with the continuous collection of detailed demographic and other information in the new American Community Survey (ACS). At the request of NSF's Science Resources Statistics Division, the Committee on National Statistics of the National Research Council formed a panel to conduct a workshop and study the issues involved in replacing the decennial census long-form sample with a sample from the ACS to serve as the frame for the information the NSF gathers. The workshop had the specific objective of identifying issues for the collection of field of degree information on the ACS with regard to goals, content, statistical methodology, data quality, and data products.

Review of the Research Program of the FreedomCAR and Fuel Partnership: Second Report - National Research Council (The National Academies Press, 2008)
The FreedomCAR and Fuel Partnership is a collaborative effort among the Department of Energy (DOE), the U.S. Council for Automotive Research (USCAR), and five major energy companies to manage research that will enable the vision of a clean and sustainable transportation energy future. It envisions a transition from more efficient internal combustion engines (ICEs), to advanced ICE hybrid electric vehicles, and to enabling a private-sector decision by 2015 on hydrogen-fueled vehicle development. At the request of DOE, the NRC has undertaken an effort to provide biennial reviews of the progress of the research program. Phase I of that review was described in a book issued in 2005. This second book presents an assessment of the progress in the research program management areas as well as the responses of program management to recommendations provided in the Phase I report. Covered in this second book are major crosscutting issues; vehicle subsystems; hydrogen production, delivery, and dispensing; and an overall assessment of the program.

Assessment of the Role of Intermittent Preventive Treatment for Malaria in Infants: Letter Report - Institute of Medicine (The National Academies Press, 2008)
Intermittent Preventive Treatment for Malaria in Infants (IPTi) is a new strategy which aims to combine the short-term protection of chemoprophylaxis with the long-term protection of naturally-acquired immunity to reduce morbidity from malaria infections during infancy. The Bill and Melinda Gates Foundation requested that the Institute of Medicine (IOM) conduct an independent assessment of the IPTi efficacy studies using sulfadoxine-pyrimethamine (IPTi-SP) that have been previously conducted by the IPTi Consortium. The IOM convened a committee to evaluate the evidence concerning IPTi-SP, which included addressing issues related to its utility and safety, as well as program management aspects of IPTi. The resulting letter report contains the findings, conclusions, and recommendations of the IOM committee. Overall, the committee found that the evidence presented makes IPTi-SP a promising public health strategy to diminish the morbidity from malaria infections, especially for the incidence of clinical malaria, among infants at high risk who reside in areas of high- or moderate-intensity transmission and is worthy of continued investment. The committee also cautioned that during large-scale implementation problems such as drug supply and logistics; monitoring and resistance; and community acceptance and reaction to IPTi-SP could arise. To maximize the greatest public health impact, the committee advised that these issues would best be addressed in an appropriate local context.

Assessing the United States Institute of Peace Jennings Randolph Senior Fellowship - National Research Council (The National Academies Press, 2008)
The United States Institute of Peace (USIP) is an independent, nonpartisan, national institution established and funded by the U.S. Congress. The goals of the USIP are to help prevent and resolve violent international conflicts; promote post-conflict stability and development; and to increase conflict management capacity, tools, and intellectual capital worldwide. One way the USIP meets those goals is through the Jennings Randolph Program for International Peace, which awards Senior Fellowships to outstanding scholars, policymakers, journalists, and other professionals from around the world to conduct research at the USIP. The Fellowship Program began in 1987, and 253 Fellowships have been awarded through 2007. This book presents a preliminary assessment of the Fellowship Program, and recommends certain steps to improve it, including more rigorous and systematic monitoring and evaluation of the Fellowship in the future. The committee also makes several recommendations intended to help USIP gain further knowledge about the perceptions of the Fellowships in the wider expert community.

Assessing the Role of K-12 Academic Standards in States: Workshop Summary - National Research Council (The National Academies Press, 2008)
Every state in the United States, the District of Columbia, and the Department of Defense Education Activity now has its own academic standards, at least in core subjects. These documents vary in their structure, level of specificity, and other characteristics. Professional societies have also developed standards, in mathematics, English language arts, science, social studies, civics, foreign languages, and other academic subjects, and many states have drawn on these as they prepared their own standards documents. Other organizations have also offered standards and benchmarks. For example, the Mid-continent Research for Education and Learning (McREL) offers standards developed with the goal of applying a consistent structure and degree of rigor and specificity to standards in diverse subjects. This abundance of standards reflects a vigorous response to the call for high standards articulated in the National Commission on Excellence in Education's 1983 report A Nation at Risk, and it also poses a variety of questions for educators, policy makers, and the public. What role are these standards playing? What are the strengths and weaknesses of the reform efforts that have been anchored by these standards? How are these standards applied, and how might standards-based reforms be improved? Would a move toward national standards in core academic subjects lead to improved instruction and learning? Would it be feasible? The committee identified three components to the charge for the first workshop: a review of the policy and research context in which current standards-based reform efforts are operating, a consideration of how the costs of standards and accountability systems might be calculated, and an analysis of similarities and differences among states' content and performance standards. Assessing the Role of K-12 Academic Standards in States: Workshop Summary summarizes this workshop and the committee's recommendations.

Test and Evaluation of Biological Standoff Detection Systems: Abbreviated Version - National Research Council (The National Academies Press, 2008)
A biological warfare agent (BWA) is a microorganism, or a toxin derived from a living organism, that causes disease in humans, plants, or animals or that causes the deterioration of material. The effectiveness of a BWA is greatly reduced if the attack is detected in time for the target population to take appropriate defensive measures. Therefore, the ability to detect a BWA, in particular to detect it before the target population is exposed, will be a valuable asset to defense against biological attacks. The ideal detection system will have quick response and be able to detect a threat plume at a distance from the target population. The development of reliable biological standoff detection systems, therefore, is a key goal. However, testing biological standoff detection systems is difficult because open-air field tests with BWAs are not permitted under international conventions and because the wide variety of environments in which detectors might be used may affect their performance. This book explores the question of how to determine whether or not a biological standoff detection system fulfills its mission reliably if we cannot conduct open-air field tests with live BWAs.

Preliminary Review of the Draft Science, Education, and Design Strategy for the Water and Environmental Research Systems (WATERS) Network - National Research Council (The National Academies Press, 2008)
One of the most critical issues facing the United States today is the proper management of our water resources. Water availability and quality are changing due to increasing population, urbanization, and land use and climate change. Despite the fact that overall water use in the U.S. has remained relatively constant since about 1980, shortages in water supply have been increasing in frequency in many parts of the country, and water quality is also declining in some areas. The National Science Foundation (NSF) has proposed the Water and Environmental Research Systems (WATERS) Network as one possible initiative whereby NSF could provide the advances in the basic science needed to respond effectively to the challenge of managing water resources. In its interim report, Preliminary Review of the Draft Science, Education, and Design Strategy for the WATER and Environmental Research Systems Network, the committee comments on the WATERS draft design strategy and provides advice in several key categories related to the WATERS plan: science questions; observatory design; sensors; cyberinfrastructure; education and outreach; and governance and management.

Research on Future Skill Demands: A Workshop Summary - National Research Council
Over the past five years, business and education groups have issued a series of reports indicating that the skill demands of work are rising, due to rapid technological change and increasing global competition. Researchers have begun to study changing workplace skill demands. Some economists have found that technological change is \

Technical Input on Any Additional Studies to Assess Risk Associated with Operation of the National Emerging Infectious Diseases Laboratory, Boston University: A Letter Report - National Research Council (The National Academies Press, 2008)

Research Priorities in Emergency Preparedness and Response for Public Health Systems: A Letter Report - Institute of Medicine (The National Academies Press, 2008)
Schools of public health act as a resource by providing expertise to strengthen our nation's emergency response systems. In response to the Pandemic and All Hazards Preparedness Act (PAHPA), there is an immediate and critical need to define research priorities for the Centers for Public Health Preparedness (CPHP) at schools of public health. It is because of this crucial need, that the Institute of Medicine (IOM) convened an ad hoc committee, conducted a fast-track study, and issued the book entitled Research Priorities in Emergency Preparedness and Response for Public Health Systems. The book defines a set of near-term research priorities for emergency preparedness and response in public health systems. These priorities will be used by the Coordinating Office for Terrorism Preparedness and Emergency Response (COPTER) to help develop a research agenda that will in turn be used to inform research funding opportunity announcements. After considering the information presented during the public meeting and workshop and based on its expert judgment, the committee identified four priority areas for research that represent specific important aspects of systems of public health preparedness. The four areas are: enhancing the usefulness of training; improving timely emergency communications; creating and maintaining sustainable response systems; and generating effectiveness criteria and metrics.